ความต้องการในการใช้งาน E-Learning ในการเรียนการสอนของอาจารย์และนักศึกษา มหาวิทยาลัยมหามกุฏราชวิทยาลัย วิทยาเขตอีสาน - ทาชา, วิทูล; สุขเสน, เอกชาตรี (วารสารการบริหารการศึกษา มมร.วิทยาเขตร้อยเอ็ด; Vol 4 No 3 (2567): กันยายน-ธันวาคม 2567, 2024)
งานวิจัยนี้มีวัตถุประสงค์ 1) เพื่อศึกษาความต้องการในการใช้งาน E-Learning ในการเรียนการสอนของอาจารย์และนักศึกษา มหาวิทยาลัยมหามกุฏราชวิทยาลัย วิทยาเขตอีสาน 2) เพื่อศึกษาข้อเสนอแนะเกี่ยวกับ E-Learning ในการเรียนการสอนของอาจารย์และนักศึกษา มหาวิทยาลัยมหามกุฏราชวิทยาลัย วิทยาเขตอีสาน กลุ่มตัวอย่างได้แก่ อาจารย์ และนักศึกษาระดับปริญญาตรี - ปริญญาเอก จำนวน 250 รูป/คน เครื่องมือที่ใช้ในการวิจัย ได้แก่ แบบสอบถาม สถิติที่ใช้ ได้แก่ ความถี่ ร้อยละ ค่าเฉลี่ย และส่วนเบ่งเบนมาตรฐาน ผลการวิจัยพบว่า 1) ความต้องการในการใช้งาน E-Learning ในการเรียนการสอนของอาจารย์และนักศึกษา มหาวิทยาลัยมหามกุฏราชวิทยาลัย วิทยาเขตอีสาน โดยรวมอยู่ในระดับมาก เมื่อพิจารณารายด้าน โดยเรียงจากค่าเฉลี่ยสูงสุดไปต่ำสุด ได้แก่ ด้านเนื้อหาหลักสูตร รองลงมาคือ ด้านระบบการเรียนการสอนผ่านเว็บ ด้านบุคลากร และ ด้านโครงสร้างพื้นฐานและการสนับสนุน ตามลำดับ 2) ข้อเสนอแนะเกี่ยวกับ E-Learning ในการเรียนการสอนของอาจารย์และนักศึกษา มหาวิทยาลัยมหามกุฏราชวิทยาลัย วิทยาเขตอีสาน ได้แก่ การเรียนรู้ต้องควบคู่กับการปฏิบัติจริง การเรียนการสอน E-learning ทางมหาวิทยาลัยสามารถจัดทำได้ แต่ก็ต้องมีเวลาหรือช่วงเวลาที่นักศึกษา และอาจารย์ได้พบปะกัน เพื่อทำความรู้ความเข้าใจในการเรียนบ้าง ตอบสนองความต้องการของผู้เรียน และความเป็นปัจเจกของผู้เรียน ซึ่งเราสามารถมอบหมายงานให้ผู้เรียนศึกษาผ่าน E-learning แล้วมาร่วมแลกเปลี่ยนเรียนรู้ในชั้นเรียนที่เรียกว่าเป็นการเรียนรู้แบบห้องเรียนกลับด้าน flipped classroom จะดีต่อการสอน แต่ไม่เห็นด้วยถ้าจะไม่เข้าชั้นเรียนเลย การเรียนรู้ผ่าน E-learning เป็นสิ่งที่ดีที่จะช่วยส่งเสริมการเรียนรู้ และผู้เรียนสามารถเรียนรู้ได้ตามอัธยาศัย ตามศักยภาพของตน The objectives of the research were 1) to study the need for using E-Learning in teaching and learning of lecturers and students of Mahamakut Buddhist University, Isan Campus and 2) to study the suggestions on E-Learning in teaching and learning of lecturers and students of Mahamakut Buddhist University, Isan Campus. The sample group consisted of 250 lecturers and undergraduate-doctoral students. The instruments were questionnaires. The statistics used were frequency, percentage, mean, and standard deviation. The research results found that 1) The need for using E-Learning in teaching and learning of lecturers and students of Mahamakut Buddhist University, Isan Campus was at a high level overall when considering each aspect, ranked from most to least, namely, course content, web-based teaching system, personnel, and infrastructure and support, respectively. 2) Suggestions on E-Learning in teaching and learning of lecturers and students of Mahamakut Buddhist University, Isan Campus were: Learning must be combined with actual practice. The university can organize E-learning teaching and learning, but there must be time or period for students and lecturers to meet to gain some understanding of the learning and respond to the needs of the learners. and the individuality of the learner, which we can assign work for the learner to study through E-learning and then come to exchange knowledge in the classroom, which is called flipped classroom learning, it will be good for teaching, but I don’t agree if we don't attend class at all. Learning through E-learning is a good thing that helps promote learning and the learner can learn at their own leisure, according to their potential.